Multi-tiered dispute resolution clauses: an approach to their main problems - Rodríguez Uriol, Dario Andrés (2023)
The multi-tiered dispute resolution clauses are a very popular type of arbitration agreement nowadays. These clauses provide that, in order to resolve disputes arising out of a contractual relationship, the parties may or should have recourse to more than one dispute resolution mechanism, which will be used progressively, one after the other. Although this type of covenants may present advantages for the parties, they may also become problematic clauses, which, when inadequately designed or managed, may be a source of additional conflicts to those already arising. For this reason, this article will analyze the main problems that arise in connection with this type of agreement. More specifically, three issues are analyzed in relation to the pre-arbitration stages: their enforceability, the most relevant factors to be taken into account for their execution and compliance, and the consequences of non-compliance for the arbitration process.